Residual life evaluation of remanufacturing blanks considering the crack closure. (November 2022) - Hua, Liang; Fang, Song; Zhou, Rundong; Shen, Linghong
The nonlinear continuous fatigue cumulative damage model proposed by Chaboche was modified considering the effect of crack closure on fatigue damage, and the fatigue cumulative damage and residual life evaluation model of remanufactured blanks was obtained. The related parameters of the modified model were obtained from the data of symmetric cyclic tensile and compression fatigue tests. The residual life evaluation model of remanufactured blanks was verified by the two-stage loading (high and low loading and low and high loading) tensile and compressive fatigue test. The results show that the calculated values of the model are in good agreement with the test values, which proves that the modified model can accurately predict the residual life of remanufactured blanks.